Looking at the Next 20 Years of Multiliteracies: A Discussion with Allan Luke. Issue 1 (2nd January 2018) - Garcia, Antero; Luke, Allan; Seglem, Robyn
Abstract : In this discussion with literacies researcher Allan Luke, the New London Group Member reflects on the role of multiliteracies in shaping literacies research and the continuing changes to technology, capitalism, and learning. Focused on looking toward future advances in literacies research, Luke reflects on the role of multiliteracies in contemporary educational policy and how this work is shaping literacy scholarship and practice today. Luke looks pragmatically at the current political landscape and emphasizes how colonial practices of technology over the past twenty years bend literacies research away from the initial optimism expressed by the New London Group. At the same time, Luke grounds contemporary literacies interpretations of technology and learning in foundational critical theorist like Freire, Illich, and Dewey. By focusing on how technology has changed schooling, power, and literacies, Luke considers what challenges loom for the theory and practice of powerful, equitable literacies in the next two decades.